New performed catheter for entry into pulmonary artery in complete transposition of great arteries. - Macartney, F J (1975)
A new performed, semi-rigid, polyethylene catheter, with built-in torque control, has been devised for entry to the pulmonary artery in complete transposition of the great arteries. It has been used 19 times in 17 patients: 18 times the pulmonary artery was entered from the right atrium (via the left atrium and ventricle) in a time between 40 s and 15 min (median 5 min); the patients' ages were 2 days to 6 years (median 8 months) and their weights were 3.1 to 13.3 kg (median 6.9 (kg: in the remaining 1 day-old patient, the procedures was terminated because of atrial flutter. The catheter was introduced into the axillary vein in 3 patients and thesaphenous or femoral vein in the remainder. It is suitable for angiocardiography, and the other heart chambers and vessels were easily entered.Thus the catheter has certain advantages over previously described methods for entry to the pulmonary artery, particularly when there is inferior vena caval thrombosis, or when angiocardiography is necessary. Its use does depend on the presence of an interatrial communication, so a method for entry to the pulmonary artery by retrograde catheterization from the axillary artery using a different catheter is also presented; this was successful in 2 patients with ventriculal sepatal defect.